Ensino de leitura a partir de unidades mínimas a jovens e adultos - SANTOS, Ana Cláudia Cunha dos (Universidade Federal do Pará, 2014)
The Experimental Analysis of Behavior has contributed expressively to the production of knowledge applied to human problem solving. The behavior analysts have been producing a variety of studies that investigate the basic processes involved in the acquisition of reading and writing performances, and teaching procedures that may develop these repertoires. Some studies have obtained positive results using procedures that establish the control by minimal units of reading, syllables, starting teaching macro units, words. However, it may be possible to teach reading using other alternative procedures. This study investigates the efficacy of a teaching program that starts teaching reading from minimal units and then macro units, using behavioral technology. Four of six participants finished the program. All participants learned to read the taught words. One participant showed generalized reading when first tested, the other three participants needed repeated tests. Two participants developed construction of dictated taught and recombined words. Results indicate control by minimal units. Further research concerning stimulus control of writing dictated words, one important relation to be learned to achieve functional literacy, is necessary.